Current Status, Problems and Solution Proposals of Small Ruminant Husbandry in Ordu - Hilal Tozlu Çelik (Turkish Journal of Agriculture: Food Science and Technology)
The Black Sea Region has a convenient structure for small ruminants in livestock activities thanks to its mountainous, rugged terrain, climate and socio-economic structure. Ordu is the third largest city of the Black Sea Region. The purpose of this research is to determine the current status of small ruminant in Ordu province and offer solutions by defining the problems.